Culture and Social Norms: Development and Application of a Model for Culturally Contextualized Communication Measurement (MC3M) - Liu, Rain W.; Lapinski, Maria K.; Kerr, John M.; Zhao, Jinhua; Bum, Tsering; Lu, Zhi (Frontiers in Communication, 2022)
Studies of social norms are common in the communication literature and are increasingly focused on cultural dynamics: studying co-cultural groups within national boundaries or comparing countries. Based on the review of the status quo in cross-cultural measurement development and our years of experience in conducting this research among a co-cultural group, this paper describes a Model for Culturally Contextualized Communication Measurement (MC³M) for intercultural and/or cross-cultural communication research. As an exemplar, we report on a program of research applying the model to develop a culturally derived measurement of social norms and the factors impacting the norm-behavior relationship for members of a unique population group (i.e., ethnically Tibetan pastoralists in Western China). The results provide preliminary evidence for the construct validity and reliability of the culturally derived scales measuring social norms and related variables. The implications, benefits, and shortcomings of the MC³M model are discussed. Recommendations for advancing both conceptual and measurement refinement in intercultural and cross-cultural communication research are provided.